2022
DOI: 10.3390/d14100868
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Communities of Ferromanganese Sedimentary Layers and Nodules of Lake Baikal (Bolshoy Ushkany Island)

Abstract: Ferromanganese (Fe-Mn) sedimentary layers and nodules occur at different depths within sediments at deep basins and ridges of Lake Baikal. We studied Fe-Mn nodules and host sediments recovered at the slope of Bolshoy Ushkany Island. Layer-by-layer 230Th/U dating analysis determined the initial age of the Fe-Mn nodule formation scattered in the sediments as 96 ± 5–131 ± 8 Ka. The distribution profiles of the main ions in the pore waters of the studied sediment are similar to those observed in the deep-sea areas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 96 publications
1
3
0
Order By: Relevance
“…According to the authors, the dissolution of the buried Fe-Mn oxide layer is ultimately controlled by AOM using SO 4 2− and/or Fe(III) as electron acceptors in deeper sediments, with the formation of an upper dynamic Fe-Mn oxide layer due to the O 2 diffusion from the water column in the sediments [ 9 , 11 ]. The hypothesis of the diagenetic formation of Fe-Mn layers resulting from the biogenic activity in the freshwater sediments of Lake Baikal corresponds to the studies by Dubinina [ 44 ], Granina [ 8 ], and Zakharova et al [ 45 ], as well as to our previous results of the study of communities in the sediments with Fe-Mn layers near Bolshoy Ushkany Island [ 22 ]. To develop this hypothesis, we investigated the diversity and structure of microbial communities in the sediments of the northern basin of Lake Baikal, where Granina [ 8 ] and Och et al [ 9 ] indicated a different type of diagenetic redistribution of Fe and Mn.…”
Section: Introductionsupporting
confidence: 86%
See 3 more Smart Citations
“…According to the authors, the dissolution of the buried Fe-Mn oxide layer is ultimately controlled by AOM using SO 4 2− and/or Fe(III) as electron acceptors in deeper sediments, with the formation of an upper dynamic Fe-Mn oxide layer due to the O 2 diffusion from the water column in the sediments [ 9 , 11 ]. The hypothesis of the diagenetic formation of Fe-Mn layers resulting from the biogenic activity in the freshwater sediments of Lake Baikal corresponds to the studies by Dubinina [ 44 ], Granina [ 8 ], and Zakharova et al [ 45 ], as well as to our previous results of the study of communities in the sediments with Fe-Mn layers near Bolshoy Ushkany Island [ 22 ]. To develop this hypothesis, we investigated the diversity and structure of microbial communities in the sediments of the northern basin of Lake Baikal, where Granina [ 8 ] and Och et al [ 9 ] indicated a different type of diagenetic redistribution of Fe and Mn.…”
Section: Introductionsupporting
confidence: 86%
“…Noteworthy is that members of Methylomirabiota , as well as the species Nitrospira , the most identical to the bacteria from the seeps enriched in Fe, were found in the microbial communities from the sediments enriched in iron of lakes Superior [ 4 ] and Constance [ 6 ]. The archaeal diversity in this sedimentary zone of Lake Baikal differed less significantly; as in other basins, chemolithotrophic ammonia-oxidizing archaea, Nitrososphaeria , dominated [ 22 , 84 ]. Among the members of this class in the sediments from Lake Baikal, we detected archaea of the orders Nitrosopumilales and Nitrososphaerales , known participants in aerobic ammonia oxidation [ 85 ].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Anaerolineaceae and Calditrichaceae have been reported as key bacterial taxa of shallow-water hydrothermal vents, involved not only in organic carbon remineralization but also in nitrogen cycling [15,42,43], and include moderate thermophilic chemoheterotrophs, which grow by fermentation of peptides or carbohydrates compounds and have been described as anaerobic digesters in several organic-rich habitats [44][45][46]. Analogously, bacteria within the orders Ardenticantales and Woesearchaeales (ammonium-oxidizing archaea) are known as key components of the microbial assemblages at hydrothermal vents, also participating in C, N, and especially Fe cycling [47][48][49]. In this regard, the reported presence of particularly high Fe concentration in the Panarea sediments [50] can explain the local proliferation of bacteria whose metabolic functions are strictly dependent Such taxonomic features largely differ from those previously reported in other Panarea or Vulcano Island hot vents, in which sulphur-oxidizing bacteria belonging to Campylobacterota (previously, Epsilonproteobacteria), such as Sulfurimonas, Arcobacter and Sulfurovum spp.…”
Section: Resultsmentioning
confidence: 99%